Effect of Deformation and Temperature Paths in Severe Plastic Deformation Using Groove Pressing on Microstructure, Texture, and Mechanical Properties of AZ31-O - Fong, Kai Soon (2016)
Processing of wrought magnesium alloy sheet by severe plastic deformation (SPD) for improving its formability is attractive so as to encourage the wider applications of the alloy. In this study, SPD by means of groove pressing (GP) was carried out on AZ31B-O magnesium sheet at different deformation paths and temperatures in order to investigate its effects on microstructure, textures, and mechanical properties. GP using an orthogonal pressing at every cycle and at a progressively decreasing temperature was found to be effectively for manufacturing fine-grained microstructures with an average grain diameter of 1.9 μm. The final microstructures were homogenous in both the transverse direction (TD) and rolling direction (RD) and consisting of fine grains of 0.6–1 μm with a small fraction of coarser grains of 3–5 μm. The increase in yield stress (YS), ultimate tensile strength (UTS), and tensile elongation after annealing was 12%, −2.9%, and 25.6%, respectively, in the RD. A good balance between fine-grained microstructure and ductility was obtained by the pressing at a constant processing temperature of 473 K. In this pressing path, average grain diameter was 3.8 μm and the increased in YS, UTS, and tensile elongation before annealing was 21.9%, 9.1%, and 19.8%, respectively, in the RD. It was shown that the texture modification combined with fine-grained microstructure contributed to the overall improvement in ductility.